2019
DOI: 10.1111/srt.12801
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo full‐field cellular‐resolution optical coherence tomography of basal cell carcinomas: A pilot study of quality and feasibility of images and diagnostic accuracy in subtypes

Abstract: Background Studies have reported the application of conventional optical coherence tomography (OCT) in the diagnosis of basal cell carcinoma (BCC). The new OCT provides cellular details similar to those in pathology slides and may reduce user learning time. This study aimed to demonstrate the quality of ex vivo full‐field cellular‐resolution OCT images and compare the diagnostic accuracy between physicians with varying pathology experience. Materials and Methods Sixty histologically confirmed BCCs were selecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…A drop of mineral oil was added to the lens and the cassette was then inserted into the imaging well of the device for scanning. The technological details of the device have been previously described 14 . Once the scanning process was completed, the entire plane of 10 to 30 microns below the cut surface of the specimen was visualized as one mosaic composed of multiple small elds of view (FOV; 800 µm x 600 µm).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A drop of mineral oil was added to the lens and the cassette was then inserted into the imaging well of the device for scanning. The technological details of the device have been previously described 14 . Once the scanning process was completed, the entire plane of 10 to 30 microns below the cut surface of the specimen was visualized as one mosaic composed of multiple small elds of view (FOV; 800 µm x 600 µm).…”
Section: Methodsmentioning
confidence: 99%
“…Once the scanning process was completed, the entire plane of 10 to 30 microns below the cut surface of the specimen was visualized as one mosaic composed of multiple small elds of view (FOV; 800 µm x 600 µm). The scanned images were stored on a connected computer for analysis 14 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al demonstrated that even a novice (without OCT experience) can read these images with 93% to 100% sensitivity and 21% to 54% specificity. However, this study was performed on paraffin-embedded thick tissue sections, which doesn't equate to the evaluation of freshly excised tissues 14 .…”
Section: Introductionmentioning
confidence: 99%
“…OCT has found clinical and preclinical applications in various medical fields such as ophthalmology, 3037 cardiology, 3840 neurology, 4143 gynecology, 44,45 dermatology, 4648 dentistry, 49,50 developmental biology, 51 urology, 5254 gastroenterology, 5557 etc. OCT has been used to measure the oxygen saturation in blood vessels by extracting the spectral information in the interference signals.…”
mentioning
confidence: 99%